Balance beam crossing times are slower after noise exposure in rats - Bartikofsky, Dylan; Hertz, Mikayla Jade; Bauer, David S.; Altschuler, Richard; King, W. Michael; Stewart, Courtney Elaine (Frontiers in Integrative Neuroscience, 2023)
Tables: 1 Total Number of Pages: 34 Contribution to the Field: Our previous work has shown noise-induced changes in VsEP amplitude and latency in the rat with reduced calyx-only afferent terminal calretinin immunoreactivity in the saccule. Although previous work highlighted a significant consequence of noise exposure at cellular and electro-physiological levels, the functional consequences of our data were unclear. The current study showed the same 120-decibel sound pressure level 1.5 kilohertz 3-octave band noise exposure paradigm that has been reported previously (6hours, free-field) significantly decreased balance beam crossing speed with a timeline of recovery to a crossing speed that is elevated from, but statistically similar to baseline 5-weeks after noise exposure. To our knowledge, this is the first study to document this time course with rigorous timing and scoring methods that strongly suggest a change in walking speed that can be linked to noise-induced vestibular injury, previously measured with VsEP and identified in saccular tissue.